INFLUENCE OF SPIRULINA ON GROWTH AND GONADAL MATURATION IN GOLDFISH, CARASSIUS AURATUS - T. Gowsalya; J. Stephen Sampath Kumar; C. Judith Betsy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out to find the influence of Spirulina on the growth and gonad maturation of goldfish, Carassius auratus. The gold fishes were stocked in troughs of 45 liters capacity and maintained with replicates. They were fed with diet supplemented with Spirulina at two concentrations viz., 10% (T11) and 15% (T12) and a control diet (basal diet) was also fed without Spirulina. The experiment was carried out for a period of 60 days. Sampling on the bio-growth parameters was done once in 10 days. At the end of feeding trial, fishes fed with Spirulina containing diet at 10% (T11) level had higher growth (30.64g) when compared to fishes fed with Spirulina containing diet at 15% level (28.56 g) and control feed (18.2 g). Histological sections were taken once in 30 days. On the 60th day of the experiment, the control group had less with immature ova but in fishes had well developed ovary with eggs in Secondary Vitellogenesis (SVO) stage as noticed in the histological sections of the ovary of T11 and T12 group. Therefore, 10% Spirulina containing diet is found optimum for growth and gonad maturation of goldfishes.